Implementation Of The Cash-Based Accounting Method In A Web-Based Mosque Financial Management Application: Case Study Of A Mosque In Bandung City - Adit Hardiansyah Surachman; Ikbal Jamaludin; Adi Suwarno; Dewi Fawziawati (LPPM STMIK Mardira Indonesia, 2026)
The financial management of a mosque in Bandung currently relies on a semi-manual system that is susceptible to input errors, duplicate records, and delays in report generation, thereby obstructing transparency and accountability. This research seeks to develop and implement a web-based financial management application that uses the Cash Basis Accounting approach, which documents activities based on cash inflows and outflows. The system is built with Laravel 10 and a MySQL database. The applied testing approach is Black-Box Testing to verify that each capability performs as specified. This research yields an information system comprising two primary interfaces: a public page for congregants that transparently displays financial reports, activity schedules, and donation information, and an admin dashboard for the centralized management of all financial data, schedules, and donations. The testing findings demonstrate that the system operates effectively, resolves the deficiencies of the previous system, and improves the efficiency and transparency of the mosque's financial management.